Autophosphorylation Mechanism of the Ser/Thr Kinase Stk1 From Staphylococcus aureus - Zheng, Weihao; Cai, Xiaodan; Li, Shuiming; Li, Zigang (Frontiers in Microbiology, 2018)
The eukaryotic-like Ser/Thr kinase Stk1 is crucial for virulence, cell wall biosynthesis and drug susceptibility in methicillin-resistant Staphylococcus aureus (S. aureus) (MRSA). Importantly, MRSA lacking Stk1 become sensitive to β-lactam antibiotics, implying that Stk1 could be an alternative target for combination therapy. However, the autophosphorylation mechanism of Stk1 remains elusive. Using a phosphoproteomic study, we identified six in vivo phosphorylated activation loop residues (Ser159, Thr161, Ser162, Thr164, Thr166 and Thr172) of Stk1, which are also phosphorylated in vitro. We further showed that cis autophosphorylation of Thr172 in the GT/S motif is essential for self-activation and kinase activity of Stk1 kinase domain (Stk1-KD), whereas the trans autophosphorylation of other activation loop serines/threonines are required for the optimal kinase activity of Stk1-KD. Moreover, substitution of the activation loop serines/threonines impaired in vivo autophosphorylation activity of kinase variants, while T172A and T172D variants were unable to autophosphorylate in the cellular content, underlining the essential role of Thr172 for Stk1 activity in vivo. This study provides insights into molecular basis for regulation of Stk1 activity from S. aureus.